Упростите выражение:а)3а+6+4а-4              б)а-5-4а-8в)-6а-6+(а+6)             г)(3а-5)-(2а-9)д)5а+4(а-2)                е)5а-3(а+2)

Упростите выражение: а)3а+6+4а-4              б)а-5-4а-8 в)-6а-6+(а+6)             г)(3а-5)-(2а-9) д)5а+4(а-2)                е)5а-3(а+2)
Гость
Ответ(ы) на вопрос:
Гость
а) 3а+6+4а-4=7а+2 б) а-5-4а-8=-3а-13 в) -6а-6+(а+6) = -6а-6+а+6=-5а г) (3а-5) - (2а-9) = 3а-5-2а+9=а+4 д) 5а+4(а-2) = 5а+4а-8=9а-8 е) 5а-3(а+2) = 5а-3а-6=2а-6
Не нашли ответ?
Ответить на вопрос
Похожие вопросы